Adult and Child Visiting at Urban Jails: Perspectives on Visitation Experiences and Policies among Visitors and People in Jail - Siegel, Jane A. (The prison journal, 2021)
Growth in the US incarcerated population over recent decades has brought a burgeoning body of research on parent-child visitations in correctional facilities. In contrast to this research, which has largely focused on prisons, this study reports survey results from over 900 visitors and incarcerated adults in an urban jail system. We center our attention on the commonality of children visiting jail incarcerated parents, the ways in which a jail system may facilitate or hamper the visitation process, and opinions on potential visiting policy modifications, including the use of video visiting. Implications for jail visitation policies are discussed.